CONCEPTS OF SCHOOL: APPROACHES TO THE CHILEAN EDUCATION SYSTEM FROM CONCEPTUAL HISTORY. 1840-1890. - Mayorga, Rodrigo (Revista de Historia Social y de las Mentalidades, 2024)
During the ninetieth century, one of the most  important concerning of the Chilean State  was to establish a public educational system  that would extend education throughout  the territory. However, the novelty of this  institution led the institutional actors to the  need of conceptualize and define the school  itself, the effects expected to be attained with  this and the means to achieve it. This article aims to investigate this process  from an approach of conceptual history.  From the postulates presented by the  historian Reinhart Koselleck, we investigate  how the institutional actors conceptualized  the role of the school, both in terms of its  modifier capacity and the effects that they  was looking to get through it. During the  period between the 1840s and 1880s, schools  were understood as institutions capable  of transforming individuals who assisted  to them, which led to the priority need of  establish uniformity by surveillance and  control. At the same time, the apparent  consensus about the civilizing role of the  school was given with a constant tension  between moralizing and modernizing  elements embedded in it, which led to  raise emphasis and nuances within the  objectives pursued by the school, but always  circumscribed within the general framework  of the transformation of individuals to benefit  the nation-state project proposed by the  ruling classes
Keywords: education; conceptual history; nation-state; ninetieth century